PROJECT BASED LEARNING IMPLEMENTATION TO ENABLE STUDENTS’ ACTIVITIES - Naeklan Simbolon (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2015)
This article is about project-based learning is a learning model that is used to enable the students. Project-based learning is learning that engages students directly in the learning process by providing a task or project to be done in groups which will produce a real product. A learning process in which students actively construct knowledge by means of constantly acquiring new information. Project based learning is an innovative learning model and a greater emphasis on contextual learning through complex activities that provide opportunities for students, working individually or in groups, and in touch with the real world. Implementation of project-based learning that can either provide capabilities that are beneficial to the students. The success of project-based learning occurs when students get motivated, active students in learning, and produce high quality work.